Clinical significance of home blood pressure measurements for the prevention and management of high blood pressure. (January 2014) - Imai, Yutaka; Hosaka, Miki; Elnagar, Noha; Satoh, Michihiro
Summary Ambulatory blood pressure (ABP) monitoring (M) provides BP information at many points on any particular day during unrestricted routine daily activities, whereas home blood pressure (HBP) monitoring provides a lot of BP information obtained under fixed times and conditions over a long period of time, thus mean values of HBP provide high reproducibility, and thus an overall superiority compared with ABP. HBP is at least equally or better able than ABP to predict hypertensive target organ damage and prognosis of cardiovascular disease. HBPM allows for ongoing disease monitoring by patients, improves adherence to antihypertensive treatment, and can provide health‐care providers with timely clinical data and direct and immediate feedback regarding diagnosis and treatment of hypertension. HBPM provides BP information in relation to time; that is, BP in the morning, in the evening and at night during sleep, and it is an essential tool for the diagnosis of white‐coat and masked hypertension. HBPM yields minimal alerting affects and no or minimal placebo effect, and can therefore distinguish small, but significant, serial changes in BP. It is thus the most practical method for monitoring BP in the day‐to‐day management of hypertension. The superiority of HBPM over ABPM and clinic BPM is apparent from almost all practical and clinical research perspectives.